ASSESSMENT OF THE EFFECT OF CONNECTIVE TISSUE CELLS ON THE REGENERATION OF THE ORAL MUCOSA - Khusanova Yu.B., Khramova N.V.,; Charyshnikova O.S., Tsiferova N.A., (Central Asian Journal of Medicine, 2025)
This study presents a comparative experimental analysis of a tissue-engineered construct composed of silk degummed gauze and allofibroblasts for the treatment of mucosal defects in rats. The dynamics of animal weight and the relative weight of internal organs did not exhibit statistically significant deviations compared to control and reference values, indicating the safety of the cell therapy and tissue engineering methods employed for the experimental animals. The proposed tissue-engineered construct effectively supports the maintenance of proliferating dermal fibroblasts within the scaffold.